Answer:? Okkkkk
Step-by-step explanation:
Lol
Answer:
Step-by-step explanation:
The chinese man ate the dog and cat meow and roof roof
Answer:
x= 3/17
Step-by-step explanation:
4x(2x+6) =8x^2(23-5)
8x^2 +24x = 144 x^2
24x = 136 x^2
24= 136 x
x=24/136
x=3/17
Answer:
x<−4
Step-by-step explanation:
7x+6<-22
7x+6-6<-22-6
7x<-28
7x/7<-28/7
x<-4
Hope it helped!
Answer:
The answer is D
Step-by-step explanation:
Since the input is -6, you input it into the equation. That would make it f(-6)=-(-6)-1 which would be equivalent to f(-6)=6-1 , as the negatives at the beginning of the equation cancel each other out and make it positive. Then you solve and get 5, which is your output. Hope I could help :)